Adaptive radiotherapy dosimetry in a challenging geometry: A model gas-filled tissue expander in a helical TomoTherapy beam. Issue 1 (1st January 2022) - Kairn, T.; Lathouras, M.; Sylvander, S. R.; Trapp, J.V.; Crowe, S.B.
Abstract: Helical TomoTherapy treatment and delivery systems (Accuray Inc, Sunnyvale, USA) allow off-line adaptation of radiotherapy treatments, with dose calculations that use MV computed tomography (CT) data acquired at treatment. This study aimed to assess the potential dosimetric effects of a gas-filled temporary tissue expander (TTE) on the accuracy of breast radiotherapy dose calculations from both the TomoTherapy treatment planning system (TPS), which uses kV CT data, and the TomoTherapy adaptive radiotherapy (ART) system, which uses MV CT data. A TomoTherapy treatment plan was created and delivered to a 3D-printed rectilinear model of a breast with implanted gas-filled TTE, including a stainless steel CO2 container, and film measurements of the delivered dose were compared against dose calculations from the TPS and ART systems. The film measurements showed that the TomoTherapy TPS provided comparatively accurate dose calculations in the 550 cm 2 volume of air that modelled the gas filling of the TTE and within the surrounding tissue-equivalent materials, except in regions where the beam was transmitted through the stainless steel CO2 container, possibly due to the volume of stainless steel being over-estimated in the kV CT images that were used to generate the treatment plan. The ART system provided more accurate dose calculations than the TPS in regions affected by the stainless steel container, but also over-estimated the dose in the air within the TTE. These results suggest that the TomoTherapy TPS and ART systems could be used to produce reliable dose calculations of breast treatments in the presence of gas-filled TTEs, if kV CT imaging options are chosen to avoid artefacts and minimise the need for density over-rides and if treatment targets that include only clinically relevant tissues, and exclude all TTE components, are used to evaluate and compare the doses calculated by both systems.